Vector coding and place coding in hippocampus share a common directional signal - Yue-Qing Zhou; Vyash Puliyadi; Xiaojing Chen; Joonhee Leo Lee; Lan-Yuan Zhang; James J. Knierim (Nature Communications)
Abstract Vector coding is a major mechanism by which neural systems represent an animal’s location in both global and local, item-based reference frames. Landmark vector cells (LVCs) in the hippocampus complement classic place cells by encoding vector relationships between the organism and specific landmarks. How these place- and vector-coding properties interact is not known. We recorded place cells and LVCs using calcium imaging of the CA1 region of freely moving rats during cue-card rotation studies. Place fields rotated around the center of the platform to follow the cue rotation, whereas the fields of simultaneously recorded LVCs rotated by the same amount around the nearby landmarks. Some neurons demonstrated conjunctive coding of both classic place field properties and LVC properties. These results demonstrate that CA1 neurons employ a common directional input, presumably provided by the head direction cell system, to encode animals’ locations in both world-centered and landmark-centered reference frames.